(untitled) (Bangladesh Veterinarian, 2022)
The prevalence of diseases of pigeon and response to treatment of bacterial disease were studied. One thousand pigeons were collected and examined to diagnose diseases following clinical history and signs, post-mortem lesions and laboratory examination. The overall prevalence of pigeon diseases was 21.9% (n = 219). Parasitic infestation was significantly (P<0.01) higher (30%) followed by bacterial (22.3%), viral (18.9%) nutritional and others (16.3%) and fungal (14.3%). Disease prevalence was higher in female than in male, and higher in birds of 2 to 6-months old than in older or younger birds. The prevalence of diseases was higher (P<0.01) in winter (34%) than summer (16.7%) and rainy (14.3%) seasons. Pigeons of extensive rearing system showed more (23.0%) infection than in intensive (19.7%) system. Prevalence was significantly (P<0.01) higher (25.2%) in nonvaccinated pigeons than vaccinated (17%) pigeons. Treatment with Oxytetracycline hydrochloride (Tetravet-200 WSP), Sulphaclozine Sodium Monohydrate (SCZ WSP) and Doxycycline (DOXY-A VET) were effective against bacterial diseases. It is suggested that scientific management, bio-security and therapeutic measures against infectious diseases are required to combat the maladies in pigeon. The Bangladesh Veterinarian (2020) 37(1 - 2): 21-26